2015
DOI: 10.1007/s00405-015-3863-7
|View full text |Cite
|
Sign up to set email alerts
|

How effective is postoperative packing in FESS patients? A critical analysis of published interventional studies

Abstract: The present study aimed to assess the clinical effectiveness of absorbable packing alone, non-absorbable packing alone, and absorbable versus non-absorbable packing in the postoperative care of FESS patients, regarding bleeding control, adhesion formation, wound healing, and overall patient comfort. Systematic literature review in Medline and other database sources until July 2013, and critical analysis of pooled data were conducted. Blinded prospective randomized control trials, prospective, and retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Less adhesions and other complications were observed with absorbable and nonabsorbable packing. 13 Also contradictory to our findings, a similar study showed an increased risk of postoperative bleeding in nostrils without packing. 32 Likewise, no significant difference in nasal congestion, pain, or postoperative bleeding was reported with nonabsorbable packing compared to absent packing.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Less adhesions and other complications were observed with absorbable and nonabsorbable packing. 13 Also contradictory to our findings, a similar study showed an increased risk of postoperative bleeding in nostrils without packing. 32 Likewise, no significant difference in nasal congestion, pain, or postoperative bleeding was reported with nonabsorbable packing compared to absent packing.…”
Section: Discussioncontrasting
confidence: 99%
“… 30 Also, the same study showed no difference in mucosal adhesions between packed and non‐packed nostrils. Moreover, results from meta‐analyses have concluded that nasal packing did not reduce bleeding post‐surgery, 13 and no significant differences in synechiae formation could be observed between no packing and various packing materials. 31 In addition, packing was not advantageous in terms of postoperative adhesion, and no‐packing methods were suggested to be a cost‐efficient alternative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent increases in the use of absorbable packing also enables patients to be discharged with nasal packing still in situ if post-operative minor haemorrhage is a concern. 20,21 There remains substantial variation between NHS hospital trusts in England in rates of day-case ESS. In the last full financial year prior to the COVID-19 pandemic a number of trusts still had overnight stay for the majority of patients.…”
Section: Discussionmentioning
confidence: 99%